Endoscopic Submucosal Dissection for Early Gastric Cancer in a Patient with Myelodysplastic Syndrome - Lim, Eun Joo; Sim, Eun Hui; Kim, Byung-Wook; Kim, Jong In; Kim, Joon Sung; Ji, Jeong-Seon; Choi, Hwang (The Korean journal of gastroenterology, 2015)
Endoscopic submucosal dissection (ESD) has been successfully performed in thrombocytopenic conditions such as in patients with liver cirrhosis but successful ESD for early gastric cancer (EGC) in hematologic diseases has rarely been reported. A 52-year-old male patient, who had previously been diagnosed with myelodysplastic syndrome 2 years ago, was admitted to our hospital for ESD of EGC. ESD was performed successfully in this patient after platelet concentrates transfusion on the day of ESD. ESD might be an option for the treatment of EGC in thrombocytopenia due to hematologic diseases when optimal supportive managements are applied. KCI Citation Count: 0